Abstracts in anthropology. (New York Baynood Pub. Co.)
Quarterly. References to journal articles, miscellaneous papers, and books, arranged under sections on archaeology, ethnology, linguistics, and physical anthropology. Cross references. Cross index.
Keywords: Anthropology -- Abstracts -- Periodicals; Language and languages -- Abstracts -- Periodicals